Rapid genome-wide profiling of DNA methylation and genetic variation using guide positioning sequencing (GPS) - Zhang, Baolong; Li, Wei; Li, Jin; Li, Yan; Luo, Huaibing; Xi, Yanping; Dong, Shihua; Wu, Feizhen; Yu, Wenqiang (Frontiers in Cell and Developmental Biology, 2024)
Whole-genome bisulfite sequencing (WGBS) has been extensively utilized for DNA methylation profiling over the past decade. However, it has shown limitations in terms of high costs and inefficiencies. The productivity and accuracy of DNA methylation detection rely critically on the optimization of methodologies and the continuous refinements of related sequencing platforms. Here, we describe a detailed protocol of guide positioning sequencing (GPS), a bisulfite-based, location-specific sequencing technology designed for comprehensive DNA methylation characterization across the genome. The fundamental principle of GPS lies in the substitution of dCTP with 5-methyl-dCTP (5 mC) at the 3′-end of DNA fragments by T4 DNA polymerase, which protects cytosines from bisulfite conversion to preserve the integrity of the base composition. This alteration allows the 3′-end to independently facilitate genetic variation profiling and guides the 5′-end, enriched with methylation information, to align more rapidly to the reference genome. Hence, GPS enables the concurrent detection of both genetic and epigenetic variations. Additionally, we provide an accessible description of the data processing, specifically involving certain software and scripts. Overall, the entire GPS procedure can be completed within a maximum of 15 days, starting with a low initial DNA input of 100–500 ng, followed by 4–5 days for library construction, 8–10 days for high-throughput sequencing (HTS) and data analysis, which can greatly facilitate the promotion and application of DNA methylation detection, especially for the rapid clinical diagnosis of diverse disease pathologies associated with concurrent genetic and epigenetic variations.